The nexus between the traditional system of governance and the local government system in Karamoja, Uganda (Commonwealth Journal of Local Governance, 2021)
In the 1990s several countries in Africa adopted decentralisation policy reforms that coincided with a renewed interest in traditional institutions. This development has since sparked an intense debate on the compatibility of traditional systems of governance with decentralisation. The present article documents a case study conducted in Uganda’s Karamoja sub-region, a stronghold of traditionalism despite local government reforms. It concludes that although the traditional system of governance could help to link local communities with the modern local government system, the two structures have not been harmonised. Instead, they run on parallel and contradictory paths, which has had negative consequences for local governance and service delivery. The paper advocates blending the two to form a hybrid system in which they complement each other rather than being a source of conflict.